HUMOR, CRITICISM, AND POWER: AN ILLOCUTIONARY SPEECH ACT IN AHMAD BAHJAT’S SHORT STORY “JUHA WA AS-SULTAN” - Ika Firnanda Pramudita; Penny Respati Yurisa (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This research aims to describe the forms of illocutionary speech acts in the short story Juḥā wa as-Sulṭān by Aḥmad Bahjat and to examine language as a medium of humor, criticism, and power negotiation. This study employs a qualitative descriptive approach using John R. Searle’s theory of speech acts, which includes five types: representative (assertive), directive, expressive, commissive, and declarative. The data consist of twelve utterances by the characters, analyzed based on their illocutionary force and contextual meaning. The results show that representative and directive illocutionary acts appear in three data points each, while expressive, commissive, and declarative acts occur in two data points respectively. Keywords : illocutionary speech acts, pragmatics, humor, social criticism, Ahmad Bahjat